Pembelajaran Sosial Emosional Pada Jenjang Sekolah Dasar - Elmira Chintiya Sari (LPPI Yayasan Almahmudi bin Dahlan, 2026)
This study aims to examine the implementation of Social Emotional Learning (SEL) in elementary schools in Indonesia using a Systematic Literature Review (SLR) approach. The study analyzes various scholarly articles published between 2019 and 2024 to identify patterns of implementation, benefits, and challenges in applying SEL. The findings indicate that SEL plays a crucial role in supporting students’ holistic development, particularly in emotional regulation, social skills, empathy, and responsible decision-making. Furthermore, SEL implementation has been shown to enhance students’ learning motivation, engagement, and the creation of a positive classroom environment. However, the implementation of SEL in elementary schools still faces several challenges, including limited teacher training, constrained curriculum time, and insufficient supporting resources. The study also reveals a gap between educational policies and actual practices in schools. Therefore, strategic efforts are needed, such as improving teacher competencies, integrating SEL into the curriculum, and strengthening sustainable educational policies. Ultimately, SEL implementation is expected to foster students who are not only academically competent but also socially and emotionally well-developed.